Regulation of the JNK3 signaling pathway during islet isolation: JNK3 and c-fos as new markers of islet quality for transplantation. - Saida Abdelli; Klearchos K Papas; Kate R Mueller; Mike P Murtaugh; Bernhard J Hering; Christophe Bonny (PLoS ONE, 2014)
Stress conditions generated throughout pancreatic islet processing initiate the activation of pro-inflammatory pathways and beta-cell destruction. Our goal is to identify relevant and preferably beta-specific markers to assess the activation of beta-cell stress and apoptotic mechanisms, and therefore the general quality of the islet preparation prior to transplantation. Protein expression and activation were analyzed by Western blotting and kinase assays. ATP measurements were performed by a luminescence-based assay. Oxygen consumption rate (OCR) was measured based on standard protocols using fiber optic sensors. Total RNA was used for gene expression analyzes. Our results indicate that pancreas digestion initiates a potent stress response in the islets by activating two stress kinases, c-Jun N-terminal Kinase (JNK) and p38. JNK1 protein levels remained unchanged between different islet preparations and following culture. In contrast, levels of JNK3 increased after islet culture, but varied markedly, with a subset of preparations bearing low JNK3 expression. The observed changes in JNK3 protein content strongly correlated with OCR measurements as determined by the Spearman's rank correlation coefficient rho [Formula: see text] in the matching islet samples, while inversely correlating with c-fos mRNA expression [Formula: see text]. In conclusion, pancreas digestion recruits JNK and p38 kinases that are known to participate to beta-cell apoptosis. Concomitantly, the islet isolation alters JNK3 and c-fos expression, both strongly correlating with OCR. Thus, a comparative analysis of JNK3 and c-fos expression before and after culture may provide for novel markers to assess islet quality prior to transplantation. JNK3 has the advantage over all other proposed markers to be islet-specific, and thus to provide for a marker independent of non-beta cell contamination.